A comparative study of the effect of two stocking levels on wool follicle development and wool production of the New Zealand Romney sheep : a thesis presented in partial fulfilment of the requirement for the degree of Master of Agricultural Science in Animal Science at Massey University - Sumner, R. M. W. (Massey University, 1969)
No abstract
Keywords: Wool production; Crossbred wool; Romney sheep; Romney Marsh sheep